The challenges of massive open online courses (MOOC)- A preliminary review - M Ejreaw, Almahdi; Mohd Drus, Sulfeeza (2017)
Massive Open Online Course (MOOC) is one of the most recent innovations in education. It is a form of an open source learning sys- tem that offers free and short online courses to anyone who has access to the Internet.MOOC offers a lifelong learning opportunity and a number of ex- isting MOOC online platforms include edX, Coursera, Udacity, and Udemy.However, there are a number of problems and challenges in MOOC, among the major recurring issue is the consistently high dropout rate of MOOC learners.In this paper, we introduce a critical review of literature relating to MOOC dropout rates, bringing together existing findings on completion rates and analyses of several specific courses related to these organizations, which identify factors that correlate to the likelihood of dropout.Finally, we discuss our findings relating MOOC dropout rates, considering what factors are within the control of an MOOC provider and suggesting the most prom- ising avenues for improvement.